The impact of plasma SOCS3 levels and endometrial leukocytes on unexplained infertility - Ozkan, Zehra Sema; Deveci, Derya; Akpolat, Nusret; Ilhan, Fulya; Simsek, Mehmet; Timurkan, Huseyin (Tubitak Scientific & Technological Research Council Turkey, 2018)
Background/aim: To investigate the possible differences in endometrial leukocyte subtype distribution between women with unexplained infertility and normal fertile women and to determine whether there is a correlation between endometrial leukocyte counts and plasma cytokine levels in unexplained infertility. Materials and methods: This case-control study involved 79 infertile and 40 fertile women. Peripheral venous blood samples and endometrial samples were obtained on day 21 of the menstrual cycle. Plasma interleukin-4 (IL4), IL6, IL10, IL17, IL35, interferongamma (IFN-g), tumor necrosis factor-alpha (TNF-a), transforming growth factor-beta (TGF-b), and suppressor of cytokine signaling-3 (SOCS3) levels were determined by enzyme-linked immunosorbent assay. Endometrial CD8, CD56, and CD163 counts were detected by immunohistochemistry. Results: CD8 and CD56 counts were significantly higher, while CD163 count was significantly lower in infertile women than in fertile women. Plasma SOCS3, IL35, and IL4 levels of the infertile group were significantly lower than those of the fertile group (P < 0.01); the remaining cytokine levels were significantly higher in the infertile group than in the fertile group (P < 0.01). Conclusion: We observed aberrant cytotoxic immune activity in infertile women. The interaction between plasma SOCS3 levels and staining degree of endometrial leukocytes may be either the reason for or result of infertility leading to unavailability of the environment for implantation.
Keywords: CD56; CD163; CD8; unexplained infertility; SOCS3